Hyperplasia of Smooth Muscle in Mild to Moderate Asthma without Changes in Cell Size or Gene Expression - Woodruff, Prescott G; Dolganov, Gregory M; Ferrando, Ronald E; Donnelly, Samantha; Hays, Steven R; Solberg, Owen D; Carter, Roderick; Wong, Hofer H; Cadbury, Peggy S; Fahy, John V (American journal of respiratory and critical care medicine, 2004)
Bronchial hyperresponsiveness in mild to moderate asthma may result from airway smooth muscle cell proliferation or acquisition of a hypercontractile phenotype. Because these cells have not been well characterized in mild to moderate asthma, we examined the morphometric and gene expression characteristics of smooth muscle cells in this subgroup of patients with asthma. Using bronchial biopsies from 14 subjects with mild to moderate asthma and 15 control subjects, we quantified smooth muscle cell morphology by stereology and the expression of a panel of genes related to a hypercontractile phenotype of airway smooth muscle, using laser microdissection and two-step real-time polymerase chain reaction. We found that airway smooth muscle cell size was similar in both groups, but cell number was nearly twofold higher in subjects with asthma (p = 0.03), and the amount of smooth muscle in the submucosa was increased 50-83% (p < 0.005). Gene expression profiling in smooth muscle cells showed no difference in the expression of genes encoding phenotypic markers in cells from healthy subjects and subjects with asthma (all p > 0.1). We conclude that airway smooth muscle proliferation is a pathologic characteristic of subjects with mild to moderate asthma. However, smooth muscle cells in mild to moderate asthma do not show hypertrophy or gene expression changes of a hypercontractile phenotype observed in vitro.